White light, black rain the destruction of Hiroshima and Nagasaki - Okazaki, Steven; HBO Documentary Films; Farallon Films; HBO Video (Firm) ([New York, N.Y.] : HBO Video, 2007)
In August 1945, the world was transformed in the blink of an eye when American forces dropped atomic bombs on Hiroshima and then Nagasaki. The destruction was unprecedented and the bombings precipitated the end of World War II. Contains archival footage and stunning photography. Interviews are from both Japanese survivors and the Americans who believed that their involvement would help end a brutal conflict.
Originally produced as a documentary film in 2007.
"During certain interviews, this film will automatically play with English subtitles. To turn them off, please use the subtitle button on your DVD remote control."
Directors of photography, Takafumi Kawasaki, Steve Condiotti, Masafumi Ichinose.
TV-14.
DVD, region 1, widescreen (16:9) presentation; Dolby Digital 2.0 stereo.
English and Japanese dialogue, English subtitles; closed-captioned.
Keywords: Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Personal narratives; Nagasaki-shi (Japan) -- History -- Bombardment, 1945 -- Personal narratives; World War, 1939-1945 -- Aerial operations, American; Atomic bomb -- Blast effect; Atomic bomb victims; Nuclear warfare -- Japan -- History -- Autobiography; Nuclear weapons -- Japan -- Autobiography; Survivors -- Japan -- Autobiography; World War II -- Japan -- Autobiography; Hiroshima-shi (Japan) -- History -- Bombardment, 1945 -- Personal narratives; Nagasaki-shi (Japan) -- History -- Bombardment, 1945 -- Personal narratives; World War, 1939-1945 -- Aerial operations, American; Atomic bomb -- Blast effect; Atomic bomb victims; Video recordings for the hearing impaired; Documentary films; Documentary -- Feature